Perancangan Bak Sampah Terpilah untuk Drop Point Bank Sampah Bersinar Menggunakan Metode Design Thinking - Fia Izzah Maylinda; Nora Hafildah; Rafi Hafizhni Anggia (INSTITUT SENI INDONESIA PADANGPANJANG, 2026)
Bersinar Waste Bank is a community based waste management facility that encourages waste segregation to be processed into products with economic value. In practice, the waste deposited by residents has already been sorted by type before the weighing process. However, after being weighed, the waste is placed directly in the yard of the Bersinar Waste Bank without further grouping before being transferred to the storage warehouse. This condition leads to waste accumulation in the drop point area, creating a cluttered appearance and reducing visual quality as well as environmental comfort. This study aims to design a set of segregated waste bins to make the Bersinar Waste Bank drop point more organized and orderly. The method used is design thinking, consisting of the empathize stage to understand user needs and activities around the waste bank, define to formulate the main problems, ideate to generate alternative design solutions, prototype to develop the concept into a generate alternative design solutions, prototype to develop the concept into a model or mock-up, and test to validate the effectiveness of the design. The result of this study is a segregated waste bin product design that considers functional aspects, ease of post weighing waste grouping, ergonomics, and visual aesthetics. This design is expected to be applicable to other waste banks to maintain a more organized and visually comfortable drop point area, while supporting more systematic and sustainable waste management.